Laser-stimulated fluorescence reveals unseen details in fossils from the Upper Jurassic Solnhofen Limestones - Luke A. Barlow; Michael Pittman; Anthony Butcher; David M. Martill; Thomas G. Kaye (Royal Society Open Science, 2021)
Laser-stimulated fluorescence (LSF) has seen increased use in palaeontological investigations in recent years. The method uses the high flux of laser light of visible wavelengths to reveal details sometimes missed by traditional long-wave ultraviolet (UV) methods using a lamp. In this study, we compare the results of LSF with UV-A-generated fluorescence on a range of fossils from the Upper Jurassic Solnhofen Limestone Konservat-Lagerstätte of Bavaria, Germany. The methodology follows previous protocols of LSF with modifications made to enhance laser beam intensity, namely keeping the laser at a constant distance from the specimen, using a camera track. Our experiments show that along with making surface details more vivid than UV-A or revealing them for the first time, LSF has the additional value of revealing shallow subsurface specimen detail. Fossil decapods from the Solnhofen Limestone reveal full body outlines, even under the matrix, along with details of segmentation within the appendages such as limbs and antennae. The results indicate that LSF can be used on invertebrate fossils along with vertebrates and may often surpass the information provided by traditional UV methods.